Supervised versus unsupervised primaquine radical cure for the treatment of falciparum and vivax malaria in Papua, Indonesia: a cluster-randomised, controlled, open-label superiority trial - Poespoprodjo, Jeanne Rini; Burdam, Faustina Helena; Candrawati, Freis; Ley, Benedikt; Simpson, Julie A.; Price, Ric N. (The Lancet Group, 2022)
Background There is a high risk of Plasmodium vivax recurrence in patients treated for Plasmodium falciparum malaria in co-endemic areas. Primaquine radical cure has the potential to reduce P vivax recurrences in patients presenting with P falciparum as well as P vivax malaria but is undermined by poor adherence to the currently recommended 14-day regimen. We aimed to assess the efficacy and safety of supervised versus unsupervised primaquine radical cure in patients presenting with uncomplicated malaria. Methods We did a cluster-randomised, controlled, open-label superiority trial in Papua, Indonesia. 21 clusters of village health posts, matched by annual parasite index, were randomly assigned (1:1) to treat patients (age >12 months and body weight >5 kg) presenting with confirmed uncomplicated P falciparum or P vivax malaria with oral dihydroartemisinin–piperaquine plus either a supervised or unsupervised 14-day course of oral primaquine (0·5 mg/kg per day). Patients in the supervised group were supervised taking their primaquine dose on alternate days. Patients were followed-up for 6 months and those who presented again with malaria were retreated with the same drug regimen. Masking was not possible due to the nature of the study. The primary outcome was the incidence risk of P vivax malaria over 6 months, assessed in the modified intention-to-treat population (all patients who were assigned to a treatment group, excluding patients who were lost to follow-up after their first visit). This trial is now complete, and is registered with ClinicalTrials.gov, NCT02787070. Findings Between Sept 14, 2016, and July 31, 2018, 436 patients were screened for eligibility and 419 were enrolled; 223 (53%) patients in 11 clusters were assigned to supervised primaquine treatment and 196 (47%) in ten clusters to unsupervised primaquine treatment. 161 (72%) of 223 patients in the supervised group and 151 (77%) of 196 in the unsupervised group completed 6 months of follow-up. At 6 months, the incidence risk of P vivax recurrence in the supervised group was 29·7% (95% CI 16·4–49·9) versus 55·8% (32·3–81·8) in the unsupervised group (hazard ratio 0·23 [95% CI 0·07–0·76]; p=0·016). The incidence rate for P vivax recurrence was 539 (95% CI 390–747) infections per 1000 person-years in the supervised group versus 859 (673–1096) in the unsupervised group (incidence rate ratio 0·63 [95% CI 0·42–0·94]; p=0·025). The corresponding rates in the 224 patients who presented with P falciparum malaria were 346 (95% CI 213–563) and 660 (446–977; incidence rate ratio 0·52 [95% CI 0·28–0·98]; p=0·043). Seven serious adverse events were reported (three in the supervised group, four in the unsupervised group), none of which were deemed treatment-related, and there were no deaths. Interpretation In this area of moderate malaria transmission, supervision of primaquine radical cure treatment reduced the risk of P vivax recurrence. This finding was apparent for patients presenting with either P falciparum or P vivax malaria. Further studies are warranted to investigate the safety and efficacy of radical cure for patients presenting with uncomplicated falciparum malaria in other co-endemic areas.